Far from Isolation: The Spatial Politics of the Relocation of the Main Campus of the University of the Philippines, 1930s–1970s - Pante, Michael D (Archīum Ateneo, 2018)
The first campus of the University of the Philippines, which was founded in 1908, was located in Ermita, Manila. Three decades later, its location in the rapidly urbanizing and politically volatile capital led university and government officials to move the university to Diliman in suburban Quezon City, a site that embodied the university town archetype. While the new campus conformed to the university town template, Quezon City’s income-poor communities proved significant in radicalizing students, thereby undermining the original intention behind Diliman. Attention to the peculiar historical geography of the main campus of the University of the Philippines has potential to serve as the start of a conversation on the socio-spatial relations between universities and Southeast Asian cities.